Surface active polymers as anti-infective and anti-biofouling materials - Parker, EM (2012)
This thesis is concerned with the chemical modification of polymers in the preparation of a library of materials which exhibit altered surface properties as a result of the surface chemical functionality, with particular emphasis on the development of materials that control biofouling and are antibacterial. Chemical modification of crosslinked polystyrene, in film and microsphere form, was carried out by carbene insertion followed by diazonium coupling. This provided access to a collection of materials with varying surface chemistry, whilst the bulk properties of the polystyrene substrates were maintained. Synthesis of the diaryldiazo and the diazonium salts used to perform the surface modifications is described, as well as the preparation and characterisation of the materials. Analysis of the ability of the materials to adsorb and bind the protein bovine serum albumin (BSA) is presented with data obtained from two methods of observation. Quartz Crystal Microbalance with Dissipation (QCM-D) and a protein assay based on the change in optical density of a BSA/PBS solution are used to demonstrate how the specific surface chemistry of the materials influences the ability to adsorb and bind protein. The behaviour of the materials was time dependent and was rationalised with respect to the surface water contact angle and the calculated parameters polar surface area and % polar surface area of the functional groups added to the surfaces. Finally, penicillin loaded materials were prepared and their antibacterial activity was tested against E. coli and S. aureus, demonstrating that the antibiotic is still active from within the polystyrene scaffold.